APPLICATION OF NANOSTRUCTURES IN ANTIMICROBIAL THERAPY - Mahavir, Joshi; Sneh, Lata; Preeti, Kanwar; Tulika, Mishra (International Journal of Applied Pharmaceutics, 2018)
There are many infectious diseases that may be biofilm mediated, medical device-mediated or from some other agent, are now becoming life-threatening. Despite of availability of many antimicrobial agents, new drugs or therapeutics, these infections have continued to be a global health challenge. Nowadays, conventional antimicrobial agents have failed against many infections due to the emergence of multiple drug-resistant strains. Even, if there is a therapeutic efficacy of these drugs, there inappropriate amounts are resulting in an adequate therapeutic index, local and systematic side effects, including irritation, reduction in gut flora and other manifestations. To overcome such situations, nanostructures have exclusive physicochemical properties as they are ultra small, their size can be controlled, greater surface area to mass ratio, high reactivity and functionalizable structure. Encapsulation of antimicrobial drugs in these nanoparticle systems helps in reducing many side effects. It also helps in the sustained release of drug for a larger time period. Several metal and metal oxide nanoparticles such as silver, gold, zinc, etc. have shown a promising antimicrobial activity. Liposomes, polymeric nanoparticles, dendrimers, and solid lipid nanoparticles have achieved great success as efficient antimicrobial drug delivery systems. These nanoparticles use multiple biological pathways to exert their antimicrobial mechanism such as cell wall disruption, inhibition of RNA synthesis, protein synthesis, etc. Moreover,these preparations of nanoparticles are more cost-effective than that of antibiotic synthesis with lesser or no side effects.